2007
DOI: 10.1007/s10194-007-0404-9
|View full text |Cite
|
Sign up to set email alerts
|

An unusual case of vascular loop syndrome

Abstract: Coexistence of hemifacial spasm (HFS) and trigeminal neuralgia (TN) is a rare entity known as painful tic convulsif (PTC). Here, we present a case of right-sided HFS after which left TN developed, which is an unusual form of PTC. Both disorders were caused by bilateral vascular compression of the cranial nerves and successfully treated with botulinum toxin and carbamazepine. As PTC is benign in nature and can be treated with botulinum toxin, neuroradiological investigations should be performed for an accurate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 6 publications
1
3
0
1
Order By: Relevance
“…From this perspective hypertension may exacerbate the arterial tortuosity at the brainstem and increase the chance of developing neurovascular compression, which in turn, contributing to a higher risk for TN [2]. Hypertension also accelerates atherosclerotic changes, causing the formation of ectatic vessels and resulting in the development of vascular compression [7]. In the present case the trigeminal nerve was compressed by a vascular loop and this finding was confirmed by MRI.…”
Section: Discussionsupporting
confidence: 71%
See 1 more Smart Citation
“…From this perspective hypertension may exacerbate the arterial tortuosity at the brainstem and increase the chance of developing neurovascular compression, which in turn, contributing to a higher risk for TN [2]. Hypertension also accelerates atherosclerotic changes, causing the formation of ectatic vessels and resulting in the development of vascular compression [7]. In the present case the trigeminal nerve was compressed by a vascular loop and this finding was confirmed by MRI.…”
Section: Discussionsupporting
confidence: 71%
“…The exact patophysiology of TN is still unknown. Although several theories have been proposed to determine the aethiology, most reports concentrate on the anatomic relation between the nerves and the juxtaposed vascular loops [7]. In majority of TN cases the trigeminal nerve root entry zone has been found to be compressed by an aberrant loop of artery or vein, which ultimately leads to demyelination of the trigeminal nerve [6].…”
Section: Discussionmentioning
confidence: 99%
“…Several case reports have suggested that botulinum toxin injected into the hyperalgesic tissue may be helpful at reducing spontaneous and provoked pain of neuropathic origin (13)(14)(15)(16)(17)(18)(19). A few small randomized clinical trials have been conducted and also suggested that botulinum toxin may be helpful in the treatment of neuropathic pain, namely painful peripheral diabetic neuropathy (20), CRPS (21), and trigeminal neuralgia (22).…”
Section: Introductionmentioning
confidence: 96%
“…Reporting a case similar to the one that motivated a previous study by our group 4 , Jankovic described a patient who presented with hemifacial spasm and TN whose TN improved after treatment of the hemifacial spasm with BoNT/A. Since then, case reports and case series have been published in neurology, headache, pharmacology and pain medicine journals 6,7,8,9,10,11,12,13,14 . This literature, although suggesting the therapeutic effects of BoNT/A in TN, has been challenged 15 or even ignored by panels of experts 16,17 .…”
mentioning
confidence: 80%